Enhancement of Skin Anti-Wrinkling Effects of Arthrospira maxima Phycocynobilin by Combining with Wheat Bran Extract - Eun-Jeong Koh; Taeho Kim; Yong-Kyun Ryu; Won-Kyu Lee; In-Yung Sunwoo; Hyang Seon Ro; Gibeom Jeon; Gyu Rae Kim; Hyeon Yong Lee; Woon-Yong Choi (Applied Sciences)
Despite the many beneficial effects of phycocyanobilin (PCB) on human skin, its cosmetic applications have not been extensively investigated owing to its light and temperature sensitivity. This is the first report of PCB extract (SP) derived from marine Arthrospira maxima having skin anti-wrinkling effects associated with antioxidant efficacy and reduction of intracellular reactive oxygen species (ROS) production. We obtained 46.63 ± 1.72 mg PCB/g dry weight of A. maxima in SP through an ethanol extraction process. PCB extracts showed strong effects in increasing collagen synthesis and decreasing matrix metalloproteinases (MMP-1) production. Interestingly, skin anti-wrinkling effects of the PCB extracts were significantly increased by the addition of wheat bran extracts (WB), up to 20–30% of the effects of PCB at all concentrations, possibly due to the synergistic effects of soluble globulins and other active substances in WB. Moreover, the mixture of SP and WB (SPWB) greatly reduced cell cytotoxicity to approximately 15% of that of PCB. SPWB upregulated and downregulated the expression of collagen type I α1 (Col1A1) and MMP-1, respectively, although the downregulation of MMP-1 was higher than that of Col1A1. The optimal SPWB concentration for maintaining the highest skin anti-wrinkling effects was 0.5 mg/mL. We show that SPWB holds promise as a vegan cosmaceutical.